The prevalence of potentially traumatic events in the seventh survey of the population-based Tromsø study (Tromsø 7) - Thimm, Jens; Rognmo, Kamilla; Rye, Marte; Flåm, Anna Margrete; Næss, Eva Therese; Skre, Ingunn; Wang, Catharina Elisabeth Arfwedson (Scandinavian Journal of Public Health, 2021)
Aims: Potentially traumatic events (PTEs) can have detrimental consequences for an individual’s physical and mental health. Exposure to PTEs is therefore increasingly assessed in population-based studies. Consistent with this trend, the most recent wave of the longitudinal population-based Tromsø study (Tromsø 7) in Northern Norway included a list of PTEs. The aim of the present study was to describe the prevalence of PTEs in the sample and examine demographic correlates of reported PTE exposure in this group. Methods: In Tromsø 7, a total of 21,083 participants aged ⩾40 years (52.5% female, mean age 57.3 years) were asked about exposure to nine PTEs that occurred in childhood, in adulthood and in the previous year. Differences between demographic groups in exposure to PTEs were examined using chi-square tests and logistic regression analyses. Results: Overall, 67% of the participants reported at least one PTE across the three time intervals. A life-threatening illness or serious accident of a loved one (36.8%) or of the respondent (24.0%) and bullying (21.5%) were the most frequently reported PTEs. Female sex, younger age, indigenous or immigrant ethnicity and higher education were associated with an increased likelihood of reporting at least one PTE. Group differences with respect to specific PTEs were observed. Conclusions: The experience of PTEs is common among the participants in the Tromsø 7 study. The current study lays the foundation for further research into the associations between PTEs and physical and mental health within the Tromsø study.